2014
DOI: 10.18632/oncotarget.2782
|View full text |Cite
|
Sign up to set email alerts
|

The T-box transcription factor, TBX3, is a key substrate of AKT3 in melanomagenesis

Abstract: The AKT3 signalling pathway plays a critical role in melanoma formation and invasion and components of this signalling cascade are therefore attractive targets for the treatment of malignant melanoma. Recent evidence show that the embryonically important TBX3 transcription factor is upregulated in a subset of melanomas and plays a key role in promoting melanoma formation and invasion, in part by repressing the cell adhesion molecule E-cadherin. We have identified TBX3 as a key substrate of AKT3 in melanomagene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…While there are instances where the three Akt isoforms are able to compensate for each other, recent research show that their tissue expression patterns and functions are different (99,100). The PI3K/Akt pathway is activated in 70% of all melanoma cases and Peres et al reported that TBX3 is a substrate and effector of this pathway in melanoma (69). Consistent with other reports, the authors demonstrated that Akt3 is the predominant isoform activated in a panel of human melanoma cell lines.…”
Section: Phosphatidylinositol 3-kinase/protein Kinase B (Pi3k/akt) Sisupporting
confidence: 71%
See 1 more Smart Citation
“…While there are instances where the three Akt isoforms are able to compensate for each other, recent research show that their tissue expression patterns and functions are different (99,100). The PI3K/Akt pathway is activated in 70% of all melanoma cases and Peres et al reported that TBX3 is a substrate and effector of this pathway in melanoma (69). Consistent with other reports, the authors demonstrated that Akt3 is the predominant isoform activated in a panel of human melanoma cell lines.…”
Section: Phosphatidylinositol 3-kinase/protein Kinase B (Pi3k/akt) Sisupporting
confidence: 71%
“…This repression was shown to be physiologically relevant because when TBX3 was silenced in metastatic melanoma cells, E-cadherin levels increased. Furthermore, TBX3 is transcriptionally indirectly upregulated by the oncoprotein BRAF V600E, which is constitutively activated in 50% of melanomas, and is a substrate and effector of AKT3, which is activated in ~70% of advanced stage melanomas where it plays a critical pro-invasive role (68,69). Importantly, TBX3 was shown to repress E-cadherin downstream of both these pathways to promote migration and invasion of melanoma cells.…”
Section: Tbx3 In Tumour Formation Invasion and Metastasismentioning
confidence: 99%
“…49,50 The ¡2186-base pair TBX3-luciferase plasmid was modified to introduce point mutations by site-directed mutagenesis using the Stratagene QuikChange system. Successful introduction of the mutation was confirmed by sequencing.…”
Section: Plasmids and Mutagenesismentioning
confidence: 99%
“…A mutation of Tbx3 was demonstrated to be closely associated with the pluripotency of embryonic stem cells and the invasiveness of cancer (6). In resectable pancreatic carcinoma (7), melanoma (8), bladder cancer (9) and colorectal cancer (10), Tbx3 was revealed to be overexpressed and associated with poor prognosis of cancer. Recently, Tbx3 was reported to serve a key role in melanoma migration and invasion by acting as a key substrate of protein kinase B and thus inducing the repression of E-cadherin (8).…”
Section: Introductionmentioning
confidence: 99%
“…In resectable pancreatic carcinoma (7), melanoma (8), bladder cancer (9) and colorectal cancer (10), Tbx3 was revealed to be overexpressed and associated with poor prognosis of cancer. Recently, Tbx3 was reported to serve a key role in melanoma migration and invasion by acting as a key substrate of protein kinase B and thus inducing the repression of E-cadherin (8). Additionally, Tbx3 is involved in the anti-proliferative event mediated by the transforming growth factor β1 signaling pathway by repressing the oncogenic Tbx2 in human breast epithelial MCF-12A cells (11).…”
Section: Introductionmentioning
confidence: 99%